Screen Media Exposure and Inhibitory Control: A Longitudinal Study From Infancy to Toddlerhood. - Uzundağ, Berna A.; Güven, İlke Nur; Sıvış, Özce; Başpınar, Gülnihal (Infancy, 2026)
Inhibitory control, a core executive function, supports children's ability to manage automatic and prepotent responses and regulate behavior. Screen media may disrupt its development by displacing activities supporting self‐regulation or overstimulating the attention system. While findings in preschoolers are mixed, infancy and toddlerhood may represent particularly sensitive periods due to young children's strong reliance on social learning and their limited ability to process screen content. This longitudinal study examined associations between toddlers' inhibitory control and both the duration and context of screen media exposure, specifically, background television and parental use of media for emotion regulation. Data were collected from 75 infants and their mothers at Time 1 (infant age range = 9–16 months; M = 11.8, SD = 1.4) and again approximately 19 months later at Time 2 (infant age M = 31.1, SD = 1.8). Mothers reported on screen time and background television at both times and on media emotion regulation at Time 2. At Time 2, children completed two inhibitory control tasks (Prohibition and Reverse Categorization), and parents rated their children's inhibitory control. Greater background television exposure at Time 2 was linked to poorer performance on both behavioral tasks. Higher screen time at Time 2 predicted shorter delay of gratification in the Prohibition Task, after controlling for age, earlier screen time, and the time interval between assessments. Parental ratings of inhibitory control were not associated with screen media use. These findings point to a potential association between greater screen exposure, namely background television and overall duration, and lower inhibitory control skills during a sensitive period, independent of parental perception.